Nitrogen‐doped tin oxide electron transport layer for stable perovskite solar cells with efficiency over 23%. Issue 2 (30th March 2022) - Mo, Yanping; Wang, Chao; Zheng, Xuntian; Zhou, Peng; Li, Jing; Yu, Xinxin; Yang, Kaizhong; Deng, Xinyu; Park, Hyesung; Huang, Fuzhi; Cheng, Yi‐Bing
Abstract: Tin oxide has made a major breakthrough in high‐efficiency perovskite solar cells (PSCs) as an efficient electron transport layer by the low‐temperature chemical bath deposition method. However, tin oxide often contains pernicious defects, resulting in unsatisfactory performance. Herein, we develop high‐quality tin oxide films via a nitrogen‐doping strategy for high‐efficiency and stable planar PSCs. The aligned energy level at the interface of doped SnO2 /perovskite, more excellent charge extraction and reduced nonradiative recombination contribute to the enhanced efficiency and stability. Correspondingly, the power conversion efficiency of the devices based on N‐SnO2 film increases to 23.41% from 20.55% of the devices based on the pristine SnO2 . The N‐SnO2 devices show an outstanding stability retaining 97.8% of the initial efficiency after steady‐state output at a maximum power point for 600 s under standard AM1.5G continuous illumination without encapsulation, while less than 50% efficiency remains for the devices based on pristine SnO2 . This simple scalable strategy has shown great promise toward highly efficient and stable PSCs. Abstract : An efficient SnO2 electron transport layer is realized by nitrogen doping during the chemical bath deposition, achieving a well‐aligned energy level, enhanced charge extraction, and reduced charge recombination, thus resulting in improved efficiency and stability.